Lah lah land: a visual exploration of Singlish - Kho, Hong Kai (Nanyang Technological University, 2023)
While Singlish has yet to be recognized as an Intangible Cultural Heritage of Singapore, the creole language is one of the most unique and distinguishable features of our culture that sets us apart from the rest of the world. It is a language that reflects Singapore’s heritage, and some may even call it an identifier. This research endeavour seeks to utilize solely visual elements to effectively communicate in Singlish, departing from the conventional text-based approaches commonly employed in most applications. “Lah Lah Land: A Visual Exploration Of Singlish” investigates the usage of Singlish in graphic form for nation-building purposes, fostering a sense of pride in the local community, and tackling the challenge of preserving the vernacular language as an organic and indigenous piece of cultural identity.